Tawāzun as Religious Approach in Post-Mining Land Management - Syamsul Hadi Untung; Yuangga Kurnia Yahya; Linda Alfionita (Religio: Jurnal Studi Agama-agama, 2021)
This study aims to examine the environmental impact of mining activities from the Islamic perspective. The issue of concern in this article is the ex-mining pits that are not reclaimed nor being rehabilitated in post-mining activities. From the standpoint of al-tawāzun al-bī’ī, good mining practices mean returning land and water's function to their original position with improved quality to maintain a balance in environmental management and minimize the resulting damage, including those that cost people's lives. For this purpose, the religious approach and values play a central role in spreading good awareness among Indonesian people, known as a religious society.